2007
DOI: 10.1016/j.heares.2007.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Projections from auditory cortex contact ascending pathways that originate in the superior olive and inferior colliculus

Abstract: The superior olivary complex (SOC) and inferior colliculus (IC) are targets of cortical projections as well as sources of major ascending auditory pathways. This study examines whether the cortical projections contact cells in the SOC or IC that project to higher levels. First, we placed an anterograde tracer into the auditory cortex to label cortico-olivary axons and a retrograde tracer into the IC to label olivocollicular cells in guinea pigs. Cortical axons contacted many labeled cells in the ipsilateral SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…It is unlikely that axons of layer VI cells travel through the IC to terminate at more caudal levels. The auditory cortex projects to a number of subcollicular targets in guinea pigs (Jacomme et al, 2003; Coomes and Schofield, 2004; Schofield et al, 2006; Peterson and Schofield, 2007). All these studies, which include experiments with the tracers used here, have identified layer V cells as the source of the projections to targets caudal to the IC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unlikely that axons of layer VI cells travel through the IC to terminate at more caudal levels. The auditory cortex projects to a number of subcollicular targets in guinea pigs (Jacomme et al, 2003; Coomes and Schofield, 2004; Schofield et al, 2006; Peterson and Schofield, 2007). All these studies, which include experiments with the tracers used here, have identified layer V cells as the source of the projections to targets caudal to the IC.…”
Section: Discussionmentioning
confidence: 99%
“…The situation is further complicated by the discovery that auditory cortex also projects directly to brainstem auditory nuclei below the IC (Feliciano et al, 1995). Recent studies suggest that these cortical projections could directly affect the ascending inputs to the IC (Schofield and Coomes, 2005; Peterson and Schofield, 2007). It seems likely that numerous corticofugal pathways could play an important role in IC function; understanding these roles will require more detailed understanding of the circuitry, including the origins and termination patterns of the direct pathway from cortex to the IC.…”
mentioning
confidence: 99%
“…FR or FD was injected into the AC because these tracers are highly effective in labeling the corticocollicular pathway (Coomes Peterson and Schofield, 2007). Two methods were used to deposit tracer across a wide expanse of the AC.…”
Section: Methodsmentioning
confidence: 99%
“…The circuitry underlying these effects is not clear. The AC projects directly to the contralateral IC, but this projection is much smaller than the ipsilateral one, and terminates exclusively in the cortical areas of the contralateral IC (Bajo and Moore, 2005; Bajo et al, 2007; Coomes Peterson and Schofield, 2007). There is no evidence of a cortical projection to the contralateral ICc, so both the excitatory and inhibitory effects of the AC on the contralateral ICc must depend on a disynaptic or multisynaptic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…There are multiple IC cell types that have been defined on morphological, connectional and physiological grounds (Peruzzi, Sivaramakrishnan and Oliver 2000; Ahuja and Wu 2007; Malmierca, Blackstad and Osen 2011). There are data suggesting that both commissural and tectothalamic cells receive axosomatic input from the AC (Coomes Peterson and Schofield 2007; Nakamoto, Sowick and Schofield 2013). However, most of the inputs from the CC system terminate in the neuropil, primarily on distal dendrites and spines (Nakamoto et al 2013), suggesting that the majority of the cell types receiving CC input and their projection targets have not yet been characterized.…”
Section: Molecular and Circuit-level Considerationsmentioning
confidence: 99%